The Characterization of "I" in The Tell Tale Heart by Edgar Allan Poe - Girsang, Martina (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
The Tell Tale Heart is one of the world's most famous short story which has been the subject of literary analysis for many years. The characterization in this story is very prominent and becomes the focus of this research. This study aims to analyze the characterization of "I". The research method used is a descriptive qualitative. The data collected is from the short story The Tell Tale Heart. The results show several characterizations of "I" as the main character. The character "I" is described as unstable and obsessed with "eagle eyes". This research shows that characterization in a story can help create a horror atmosphere and increase the suspense of a story which can provide more insight into how characterization can influence the reader and enhance the reading experience. This research is expected to provide additional information for future researchers who wish to examine the short story "The Tell-Tale Heart.